KOMODIFIKASI: CERMIN RETAK AGAMA DI TELEVISI: PERSPEKTIF EKONOMI POLITIK MEDIA - Muhamad Fahrudin Yusuf (IAIN Salatiga, 2016)
Co-modification of religion has been penetrating on commercial television in Indonesia for long time. The program produced by Indosiar “Mamah dan Aa Beraksi”, “Islam itu Indah” launched by Trans TV, a soap opera entitled “Tukang Bubur Naik Haji” played on RCTI, an Indian serial film entitled “Jodha Akbar” and imported Turkish Film “Abad Kejayaan” played on ANTV, and similar drama entitled “Cermin Kehidupan” played on Trans 7 are some examples of the programs. Based on the observation and writer’s thought, it was found that the preacher, contents of program, even the audiences includethe religion into the program and it was interrupted with capitalism. In the other hand, Religion should be avoided from this case.AbstrakKomodifikasi agama telah lama merambah di televisi komersial di Indonesia. Dari program “Mamah dan Aa Beraksi” Di Indosiar dan “Islam Itu Indah” di Trans TV hingga sinetron “Tukang Bubur Naik Haji” (TBNH) di RCTI, film seri India “Jodha Akbar” dan drama seri impor Turki “Abad Kejayaan” di ANTV dan acara serupa seperi sinetron “Cermin Kehidupan” di Trans 7. Melalui pengamatan sekilas dan studi pemikiran penulis didapati temuan bahwa dai, konten hingga audiens agama yang semestinya berada di luar area kontestasi.tak luput dari kepentingan kapital itu.